Tomiyamichthys hyacinthinus, a new species of shrimpgoby (Teleostei: Gobiidae) from southern Japan - Sato, Masayuki C.; Motomura, Hiroyuki (Zootaxa, 2025)
Tomiyamichthys hyacinthinus sp. nov. is described on the basis of four specimens from Kyushu, southern Japan. The new species is characterized by the following combination of characters: VI-I, 9 dorsal-fin rays; I, 9 anal-fin rays; 17 pectoral-fin rays; 45–48 lateral and 14–15 transverse scale rows; 4 + 8 or 9 (9) gill rakers of first gill arch; partially scaled prepelvic region; a pale blotch between fourth and fifth spines of first dorsal fin; second and third spines of first dorsal fin elongated, filamentous with orange bands in males; fourth spine of first dorsal fin longer than first in males; first dorsal fin trapezoid and dorsal-fin spines non-filamentous in females; 2 or 3 transverse rows of yellow blotches anteriorly and longitudinal yellow blotches posteriorly on caudal-fin membrane. Comparative molecular analysis reveals that the new species demonstrates significant genetic divergence (9.1–10.6%) in the mitochondrial COI gene from its closest congener, T. latruncularius. The new species exhibits a distinctive ecological association with the snapping shrimp Alpheus randalli, inhabiting sandy bottoms at depths of 18 m. Tomiyamichthys hyacinthinus sp. nov. is currently known only from southern Japan.